(untitled) (Journal of Economic Research & Business Administration, 2023)
Numerous factors influence competitiveness in the global oilseed market, including technological innovations, trade policies, consumer preferences, and pricing strategies. This article emphasizes the need for further research in this field to enhance understanding and optimize competitiveness in the dynamic oilseed industry. Over the past 25 years, global oilseed production has doubled due to increasing demand for vegetable oils driven by factors such as rising food consumption in developing countries, industrial utilization of vegetable oils, dietary shifts favoring plant-based oils, and biofuel adoption. Oilseeds are not only important for human nutrition but also serve as oilseed meal being crucial for animal nutrition. The objective of this research is to assess the competitiveness of major oilseed exporters in the market using the Competitiveness Growth Index. The article tests the hypothesis that "the competitiveness of Brazil’s soybean exports continues to surpass that of the United States between 2010 and 2020." Empirical methods are used to substantiate this hypothesis, such as revealed comparative advantage and comparison of country values. The Competitiveness Growth Index is utilized to evaluate the competitiveness of oilseed exports collectively and for each major oilseed among the top six exporters. Through the calculation of the competitiveness growth index, the article demonstrates the increasing competitiveness of Brazilian oilseeds and the declining competitiveness of the United States over a 10-year period. Brazil has emerged as the world’s largest oilseed exporter, competing directly with the United States in soybean exports. In the context of growing trade liberalization, globalization, and reduced agricultural subsidies, the competitiveness of the oilseed sector holds strategic importance. As competition among producer regions intensifies, the significance of competitiveness further amplifies. Ongoing research in this area will contribute to a better understanding of the factors impacting competitiveness in the oilseed market and facilitate strategic decision-making for industry participants. Keywords: Agricultural trade, oilseeds, competitiveness, Brazil, global oilseed market, supply, and demand